Prediksi Nilai Inflasi Post Covid 19 di Indonesia - Wahyuni, Ajeng (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The COVID-19 pandemic has positively impacted inflation in Indonesia, where inflation decreased to 1.33 in June 2021. It would be better if Indonesia could maintain this figure, but in July 2021, the inflation rate began to rise again; even in April 2022, the inflation rate reached 3.47. This study will predict the inflation value after the covid-19 pandemic using Autoregressive Moving Average (ARIMA) analysis. Using monthly time-series data, we study inflation in Indonesia during the period 2010 – 2022, then predict the inflation value in the following months using Autoregressive Moving Average (ARIMA) analysis. The data is stationary at the first difference. Several possible ARIMA models analyzed show that the ARIMA (1,1,1) model was chosen as the best model. The results of this study indicate that monthly inflation in Indonesia is likely to continue to rise. The government is expected to make appropriate policies to reduce inflation based on these results.